Acidic Matrix Protein, Pif, Is a Key Macromolecule for Nacre Formation - Suzuki, Michio; Saruwatari, Kazuko; Kogure, Toshihiro; Yamamoto, Yuya; Nishimura, Tatsuya; Kato, Takashi; Nagasawa, Hiromichi (Science (American Association for the Advancement of Science), 2009)
The mollusk shell is a hard tissue consisting of calcium carbonate crystals and an organic matrix. The nacre of the shell is characterized by a stacked compartment structure with a uniformly oriented c axis of aragonite crystals in each compartment. Using a calcium carbonate-binding assay, we identified an acidic matrix protein, Pif, in the pearl oyster Pinctada fucata that specifically binds to aragonite crystals. The Pif complementary DNA (cDNA) encoded a precursor protein, which was posttranslationally cleaved to produce Pif 97 and Pif 80. The results from immunolocalization, a knockdown experiment that used RNA interference, and in vitro calcium carbonate crystallization studies strongly indicate that Pif regulates nacre formation.